Beneficial Ownership – Demand for Transparency, Threat to Privacy - Cindori, Sonja (Review of European and Comparative Law, 2023)
The basic idea behind establishing the register of beneficial owners is to increase the transparency and accessibility of data on beneficial ownership of companies and other legal entities with the aim of ensuring the public availability of data on domestic and foreign natural and legal persons. However, the possibility of the data being accessible to the general public instead of to persons or organizations that can demonstrate a legitimate interest raised the issue of violating the principles of respect for private or family life and the protection of personal data. Consequently, this raises the question of drawing the line between contributing to the common good and fighting against money laundering and terrorist financing, on the one hand, and protecting personal data, with the possibility of their misuse, on the other. A balance as well as a response to the possibility of setting soft limits of legitimate interest that would result in the achievement of all set goals was sought in the practice of the European Court of Justice. One of the legislative solutions regarding the extent of access to data on beneficial owners for the entire public, along with the establishment of different types of registers in order to prevent money laundering and terrorist financing, is described using the example of Croatia.